An exceptional role of small magnetic particles in magnetism and paleomagnetism of rocks - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2021)
Here we present the results of the investigation of basalts of the Pleistocene to Quaternary age from southern Slovakia, Miocene to Pliocene age basalts from České Středohoří Mts., North Bohemia, Cretaceous age basalts from the Syrian Arab Republic and the Cretaceous age basalts from Nigeria. The selected basalts have the reversed or at least anomalous, partly reversed RM. These types of basalts contain either dominant, or at least small part of Ti-rich titanomagnetites (Ti-Mt-es) and a more oxidized magnetic phase, probably titanomaghemite (Ti-Mgh). The reversed RM was acquired during cooling of magma from about 400 to 500°C (mostly of 450°C) to atmospheric temperature in the nature. The laboratory experiments have proven that κ of these basalts reached the maximum value in the interval 400 to 500°C, mostly at 450°C. Such behaviour of κ coincides with the results of continual measurements of the change of κ of the Ti-Mt-es with temperature. During inducing partial thermoremanent magnetization (PTRM) in the samples, the minimum value of the PTRM has been reached at the temperatures corresponding to maximum values of κ. This behaviour supports the idea that the above mentioned maximum κ corresponds to a presence of superparamagnetic (SP), small magnetic particles in the respective basalts. This is a very important phenomenon. Rather similar behaviour of κ was registered in basaltic andesites and other intermediate andesites containing residual portions of the T-rich Ti-Mt-es, from volcanic fields of central and eastern Slovakia. I deduce, that the above described behaviour of Ti-rich Ti-Mt-es with a secondary Ti-Mgh, and an acquisition of the self-reversed PTRM by the small magnetic particles in the rocks, is a general world-wide phenomenon. All results have proven very strong tendency in favour of the self-reversal PTRM of the rocks with small magnetic particles.